Overcoming Limitations in Surface Geometry‐Driven Bubble Transport: Bidirectional and Unrestricted Movement of an Underwater Gas Bubble Using a Magnetocontrollable Nonwetting Surface. (17th April 2021) - Han, Kiduk; Yong, Kijung
Abstract: The movement of underwater gas bubbles significantly affects the core processes of a variety of applications in water electrolysis, heat transfer, optofluidics, and other fields. To maneuver the motion of bubbles, surface geometry‐driven transport is widely applied by employing asymmetric nonwetting surfaces, which induce Laplace pressure based on the bubble radius differences in confined states. Although this method has successfully demonstrated bubble manipulations in various geometries, it has inevitably shown some critical limitations; gas bubbles move unidirectionally from tip to root direction and cease their movements upon reaching unconfined states. This unidirectional and local bubble transport restrains the method's applicability to many fields, and overcoming this obstacle still remains an enormous challenge. Herein, a magnetocontrollable lubricant‐infused surface (MCLIS) is introduced as a key solution to this issue. MCLISs manipulate the adhesion of gas bubbles by controlling magneto‐responsive microwire alignments and rendering two reversible adhesion states, sticky (upright) and slippery (laying wires). This unique characteristic of MCLISs enables the bidirectional and geometry‐unrestricted transportation of bubbles by the wire geometry‐gradient force ( F wgg ) generated at sticky–slippery interfaces. Furthermore, this novel magnetic responsive surface supports anti‐buoyancy transport and presents promising applications in microreactors and optical laser shutters in aqueous media. Abstract : A magnetocontrollable lubricant‐infused surface (MCLIS) is introduced to overcome limitations in conventional surface geometry‐driven bubble transport. Bidirectional and geometry‐unrestricted bubble movement is enabled by the MCLIS's unique characteristics. The MCLIS can reversibly control the adhesion and motion resistance of bubbles with magnetic field application and demonstrates anti‐buoyancy bubble transportation and fascinating applications in microreactors and optical laser shutters.